Para uma ética da humanidade: um estudo sobre filosofia prática na obra de Gerd Bornheim - Taufer, Lucas (My University, 2022)
Our aim in this master's thesis is to answer the question of whether an original philosophical ethics can be seized in Gerd Bornheim's work. We built this research into three basic steps. Firstly, we try to present the elements of philosophical ethics as understood and developed by the author. Then, we seek to identify the possible intuitions, ideas and concepts of philosophical ethics problematized by him. Finally, we intend to discuss the categories presented and identified by taking as reference the main concepts carried out by Gerd Bornheim, in order to critically synthesize the elements of philosophical ethics present in his work, to comprehend whether there is any possible originality there. Therefore, we direct our efforts as follows: after a brief introduction, we present, in the first two sections, respectively, "The bourgeois drama" and "Ethics as a problem", our attempt to comply with the first two steps postulated for this study. In the following section, entitled "Totalizing difference", we intend to develop the third of the steps mentioned above, and thus build a possible answer to the problem posed for this research. Finally, in our concluding remarks, we bring an overview of the study pointing out some key highlights. From philosophical ethics, Gerd Bornheim treats less as the search for a founded normativity, than as the human being's experiential education process towards its responsibility. In short, it is the human being formation process for gregarious life that originates, precisely, in the experience of its own contradictions, and takes place through the singular game between the theoretical and practical dimensions of its own being, that is, it emanates from the sense of own human condition. And this is precisely why we argue for an "ethics of humanity": the meaning of the concept of humanity, here, therefore, is far beyond than a universal sign under which the whole set of particular human individuals is referred. It would be such an ethics that it would ontologically turn possible the reconciliation of the original split that occurred in the Neolithic revolution, namely, between both ontological dimensions of human being, that of the rational animal and that of the political animal, thus how they reconciled in the paths of the industrial revolution, both theoretical and practical dimensions of the rational animal? Thus, the bases by which the relationships between the individual and the norm are established would be reconfigured, coextensive as they are to all human experience, either by the new understanding of the concept of the individual, or by the new meaning that normativity could capture in the institution of the responsible agency by invention and situational immersion? How are these problems related to the modernity's deadlock and the crisis of the bourgeois project? What do they have to do with the perplexity of both contemporary individual and the crisis of the groundworks of normativity? And, to what extent they based on the comprehension of the sense and the recognition of the alterity? Such are our issues. [resumo fornecido pelo autor]
Esta dissertação de mestrado tem como finalidade responder à questão de se há uma ética filosófica própria à obra de Gerd Bornheim a ser apreendida. Construímos o estudo em três etapas básicas. Na primeira, procuramos apresentar os elementos de ética filosófica como compreendidos e desenvolvidos pelo autor. Em seguida, buscamos identificar as possíveis intuições, ideias e conceitos de ética filosófica por ele problematizadas. Por fim, intentamos discutir as categorias apresentadas e identificadas ao tomar como referência os conceitos realizados por Gerd Bornheim, de modo a sintetizar criticamente os elementos de ética filosófica presentes em sua obra, com vistas a compreender sua possível originalidade. Para tanto, direcionamos nossos esforços do seguinte modo: após uma breve introdução, apresentamos, nos dois primeiros capítulos, respectivamente, "O drama burguês" e "A ética como problema", nossa tentativa de cumprir com as duas primeiras etapas postuladas para o estudo. Já no capítulo seguinte, intitulado "Diferença totalizante", pretendemos desenvolver a terceira das etapas acima mencionadas, e, assim, construir uma resposta ao problema colocado para esta pesquisa. Finalmente, nas considerações finais, trazemos um apanhado geral deste estudo. Da ética filosófica, portanto, Gerd Bornheim trata menos como a busca por uma normatividade fundamentada, do que como o processo educativo experiencial do ser humano para a responsabilidade. Em uma palavra: é a formação do homem para a vida gregária que se origina, justamente, na vivência de suas próprias contradições, e se dá pelo jogo singular entre as dimensões teórica e prática de seu próprio ser, ou seja, emana do sentido da própria condição humana. E é precisamente por isso que dizemos uma ética da humanidade: o sentido do conceito de humanidade, aqui, portanto, está para muito além de um signo universal sob o qual todo o conjunto de indivíduos particulares se remete. Seria uma ética de tal sorte a que possibilitaria ontologicamente a reconciliação da cisão originária ocorrida na revolução neolítica, a saber, entre ambas as dimensões ontológicas do homem, a do animal racional e a do animal político, destarte como se reconciliaram, nas veredas da revolução industrial, ambas as dimensões teórica e prática do animal racional? Reconfigurar-se-iam, assim, as bases pelas quais as relações entre indivíduo e norma se estabelecem, coextensivas que são à toda a experiência humana, seja pela nova compreensão do conceito de indivíduo, seja pelo novo sentido que a normatividade poderia apreender na instituição do ato responsável por invenção e imersão situacional? De que modo tais problemas estão relacionadas com o impasse da modernidade e a crise do projeto burguês? O que têm a ver com a perplexidade do indivíduo e a crise dos fundamentos da normatividade contemporâneos? E, em que medida estão fundados na compreensão do sentido e no reconhecimento da alteridade? Eis nossas questões. [resumo fornecido pelo autor]
Keywords: Bornheim, Gerd, 1929-2002; Ética; Ontologia; Dialética; Filosofia; Ethics; Ontology; Dialectic; Philosophy